Collaborative Discussion in Vocabulary Learning through Short Stories: Students’ Perceptions in an Indonesian EFL Context - Astuti Alawiyah Asti; Yanti Rosalinah (FOSTER: Journal of English Language Teaching, 2025)
Vocabulary acquisition is a major challenge in learning English as a Foreign Language (EFL), but research exploring students' perceptions of vocabulary learning through collaborative discussion is still limited. This study explores the perceptions of students at SMP Harapan Cibiutng regarding vocabulary learning through short stories using a collaborative discussion approach. Using a descriptive qualitative method, three participants from grade IX (high, medium, and low levels) were interviewed and observed. The results of the study show four main findings: 1) Students applied gradual scaffolding at three levels of ZPD (individual-peer-teacher); 2) Collaborative discussion resulted in psychological transformations including cognitive changes (from not understanding to understanding), affective changes (from doubt to confidence), and social changes (from individual to group); 3) Functional vocabulary was used to understand the story content and communicate; 4) Learning took place through the construction of shared knowledge, which included horizontal scaffolding, dialogic learning, and affective solidarity. These findings indicate that vocabulary learning through short stories with collaborative discussion is a comprehensive process involving gradual stages, social cooperation, and the use of functional vocabulary. This study provides practical implications for teachers in applying a gradual scaffolding model and creating a learning environment that supports students' psychological transformation.